DAMPAK PEMBANGUNAN INFRASTRUKTUR TERHADAP PENINGKATAN AKTIVITAS PEREKONOMIAN PASAR SENTRAL KABUPATEN SUPIORI - Tambuku, Heynce; Rante, Harmonis; Ana Rusim, Dewi (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The Central Market of the Supiori Regency is one of the economic centres in the Supiori Regency.However, in its development, it did not turn out as expected. The market was abandoned by the traders whopreferred to sell along the streets of Sorendiweri City, the capital of Supiori Regency. This has caused the mainroad in Sorendiweri City, which is used as a trading area, to be filled with scattered trash. Vehicle drivers passingthrough the location become uncomfortable and disturbed because the vendors occupy half the road to sell theirgoods. This research has two objectives, namely, first, to identify and analyze the factors causing traders to preferselling on the main road within the city of Sorendiweri rather than at the Central Market, and second, to identifyand analyze the local government's policy strategies in building new infrastructure to improve accessibility to theCentral Market. This research uses qualitative descriptive analysis to analyze the data.